Improving Arabic Writing Skills Through The Effectiveness of Imla' Manzhur Learning - Hatami, Azmil; Amrulloh, Muhammad Afif (Institut Agama Islam Negeri Palangka Raya, 2025)
Arabic writing skills are crucial for Madrasah Tsanawiyah (MTs) students however, many still face challenges in mastering them, including those at MTs Al Hikmah Bandar Lampung. A key factor contributing to these difficulties is the students' limited foundational knowledge of the Arabic language. The Imla' Manzhur learning method is regarded as an important subject of research due to its potential to enhance students' writing abilities through visual memory reinforcement and direct writing practice. This research examines the impact of the Imla' Manzhur approach on enhancing seventh grade students' ability to write in Arabic at MTs Al Hikmah Bandar Lampung. A quantitative research approach was employed, utilizing a simple experimental design. The findings indicate that the implementation of the Imla' Manzhur method significantly improved students' writing proficiency, as evidenced by the post-test average score of the experimental group reaching 80.00, compared to 59.64 in the control group. Statistical analysis using a t-test revealed a significant result (p < 0.05), confirming the method's effectiveness in Arabic language instruction. These findings suggest that the Imla' Manzhur method can serve as a valuable recommendation for Arabic language teaching in madrasah.